Sclerotiorin inhibits protein kinase G from Mycobacterium tuberculosis and impairs mycobacterial growth in macrophages - Chen, Dongni; Ma, Shuangshuang; He, Lei; Yuan, Peibo; She, Zhigang; Lu, Yongjun (Tuberculosis (Edinburgh, Scotland), 2017)
As a eukaryotic-like Ser/Thr protein kinase, Mycobacterium tuberculosis virulent effector protein kinase G (PknG) mediates mycobacterial survival by regulating bacterial cell metabolic processes and preventing phagosome-lysosome fusion in host macrophages. Targeting PknG is an effective strategy for development of anti-tuberculosis (TB) drugs. In the study, we found that sclerotiorin, derived from marine fungi from the South China Sea, exhibited moderately strong inhibitory effects on recombinant PknG, with an IC50 value of 76.5 μM, and acted as a non-competitive inhibitor. The dissociation constant (KD) of sclerotiorin determined by MST was 11.4 μM, demonstrating a moderate binding strength between them. Sclerotiorin could substantially impair the mycobacterial survival in infected macrophages while the macrophage viability remained unaffected, though it did not inhibit the mycobacterial growth in culture. When sclerotiorin was used in combination with rifampicin, intracellular mycobacterial growth decreased as sclerotiorin concentration increased. Docking analysis suggested a binding mechanism of inhibition with performing interactions with the P-loop and catalytic loop of PknG. In summary, we reported that sclerotiorin had moderately strong PknG inhibitory activity, but no cytotoxicity, and it could substantially decrease the mycobacterial growth inside macrophages, suggesting that sclerotiorin has potential to supplement antibiotic therapy for TB.